2012
DOI: 10.1021/ic202727k
|View full text |Cite
|
Sign up to set email alerts
|

The μ3Model of Acids and Bases: Extending the Lewis Theory to Intermetallics

Abstract: A central challenge in the design of new metallic materials is the elucidation of the chemical factors underlying the structures of intermetallic compounds. Analogies to molecular bonding phenomena, such as the Zintl concept, have proven very productive in approaching this goal. In this Article, we extend a foundational concept of molecular chemistry to intermetallics: the Lewis theory of acids and bases. The connection is developed through the method of moments, as applied to DFT-calibrated Hückel calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 94 publications
1
26
0
Order By: Relevance
“…A detailed examination of the dependence of the DOS curve shape on μ 3 and μ 4 leads quickly to the conclusion that μ 4 controls the depth of this pseudogap, while the number of states above and below the gap is determined by μ 3 . 34 Already, then, in the third moment we have found a measure of how well a DOS distribution is suited to its population by electrons. This is shown in Fig.…”
Section: The μ 3 -Acidity Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…A detailed examination of the dependence of the DOS curve shape on μ 3 and μ 4 leads quickly to the conclusion that μ 4 controls the depth of this pseudogap, while the number of states above and below the gap is determined by μ 3 . 34 Already, then, in the third moment we have found a measure of how well a DOS distribution is suited to its population by electrons. This is shown in Fig.…”
Section: The μ 3 -Acidity Analysismentioning
confidence: 99%
“…By exploring how the total energy of the DOS curve with a particular BF depends on μ 3 and μ 4 , we have found that ideal values of μ 3 occur for other BFs as well. 34 For a given BF value, the lowest total energy is obtained for a DOS distribution consisting of a simple pair of δ-functions, with the area under the lower energy peak being just sufficient to accept all electrons in the system.…”
Section: The μ 3 -Acidity Analysismentioning
confidence: 99%
See 3 more Smart Citations